Advancing the physics of cosmic distances: proceeding of the 289th Symposium of the International Astronomical Union held in Beijing, China, August 27 - 31, 2012 - Grijs, Richard de (Proceedings of the ... symposium of the International Astronomical Union, 2013)
Literaturangaben